Les constructions de la vision - Hakim, Mona (CV Photo, 2003)
Abstract With Parages, Alain Paiement continues his research on the modes of apprehension and representation of space in his main fields of interest, dealing with photography, architecture, cartography, and painting. Here, the rooms of the building in which the artist lives are the subjects of immense frontal-shot photographs hung and arranged in successive layers in the UQAM gallery. Paiement thus multiplies and complexifies points of view in order to destabilize our perception of our own space or, more generally, of our relationship with the world. His exploration of optical phenomena also provides a pretext for exposing the transmutable and precarious character of all forms of structure — perceptual, spatial, or architectural.